The Mw 8.1 2014 Iquique, Chile, seismic sequence: a tale of foreshocks and aftershocks. Issue 3 (3rd February 2016) - Cesca, S.; Grigoli, F.; Heimann, S.; Dahm, T.; Kriegerowski, M.; Sobiesiak, M.; Tassara, C.; Olcay, M.
Abstract: The 2014 April 1, M w 8.1 Iquique (Chile) earthquake struck in the Northern Chile seismic gap. With a rupture length of less than 200 km, it left unbroken large segments of the former gap. Early studies were able to model the main rupture features but results are ambiguous with respect to the role of aseismic slip and left open questions on the remaining hazard at the Northern Chile gap. A striking observation of the 2014 earthquake has been its extensive preparation phase, with more than 1300 events with magnitude above M L 3, occurring during the 15 months preceding the main shock. Increasing seismicity rates and observed peak magnitudes accompanied the last three weeks before the main shock. Thanks to the large data sets of regional recordings, we assess the precursor activity, compare foreshocks and aftershocks and model rupture preparation and rupture effects. To tackle inversion challenges for moderate events with an asymmetric network geometry, we use full waveforms techniques to locate events, map the seismicity rate and derive source parameters, obtaining moment tensors for more than 300 events (magnitudes M w 4.0–8.1) in the period 2013 January 1–2014 April 30. This unique data set of fore- and aftershocks is investigated to distinguish rupture process models and models of strain and stress rotation during an earthquake. Results indicate that the spatial distributions of foreshocks delineated the shallower part of the rupture areas of the main shock and its largest aftershock, well matching the spatial extension of the aftershocks cloud. Most moment tensors correspond to almost pure double couple thrust mechanisms, consistent with the slab orientation. Whereas no significant differences are observed among thrust mechanisms in different areas, nor among thrust foreshocks and aftershocks, the early aftershock sequence is characterized by the presence of normal fault mechanisms, striking parallel to the trench but dipping westward. These events likely occurred in the shallow wedge structure close to the slab interface and are consequence of the increased extensional stress in this region after the largest events. The overall stress inversion result suggests a minor stress rotation after the main shock, but a significant release of the deviatoric stress. The temporal change in the distribution of focal mechanisms can also be explained in terms of the spatial heterogeneity of the stress field: under such interpretation, the potential of a large megathrust earthquake breaking a larger segment offshore Northern Chile remains high.